Resepsi Berita Pemakzulan Presiden Jokowi pada Portal Berita Tempo.co - Syifa Syarifah Alamiyah; Simamora, Anatia (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study examines readers' reception of news regarding the impeachment of President Jokowi on the Tempo.co news portal. In its reporting, Tempo presents various opinions and statements from both supporters and opponents of the impeachment issue, as well as public reactions to the matter. Mass media plays a crucial role in shaping public opinion; however, reception analysis shows that the meaning-making process by the audience is influenced by various contextual factors. The aim of this research is to understand how readers receive news about President Jokowi's impeachment on Tempo.co. The methodology employed is qualitative descriptive, with data collected through in-depth interviews. The findings indicate that nearly all readers believe Tempo is not neutral in its reporting on Jokowi's impeachment. In reception analysis, Stuart Hall categorizes readers' acceptance into three positions; however, regarding the reception of news on Jokowi's impeachment in Tempo, only two positions were identified, with the majority of readers occupying a dominant hegemonic position.